The Story of a Discovery: Two Documents of the Same Style - Bargmanas, Chaimas (Genocidas ir rezistencija, 2010)
As is known, a group of prisoners of the ninth Kaunas fort – cremators – escaped from this prison, which was converted into the 1005-B organization at the end of 1943 (researchers have already found out that the code 1005-B indicates that we are dealing with the destruction of corpses). The day after the escape, a group of escapees, having infiltrated the Kaunas ghetto, wrote an act there about their stay in the fort and the revealed Nazi atrocities. The document was written in Russian – the ghetto underground planned to hand it over to the top leadership of the Russian army. The text of the act was not published in Soviet times: if we examine the document more closely, we will find a number of facts in it that contradict the concepts of the then government. In the autumn of 1983, the author of these lines managed to copy the text of the act from the copy kept by Izraelis Veselnitskis – one of the organizers of the escape.
Keywords: Lithutnia; German occupation; Holocaust; 9th fort; Kaunas